Застосування творчих методів навчання для формування професійної комунікативної компетентності майбутніх поліцейських - Голопич, І. М.; Golopych, І. М. (Педагогічні науки: теорія, історія, інноваційні технології. - 2020. - № 7. - С. 23-33, 2020)
Висвітлено можливості використання творчих методів навчання на заняттях з української мови професійного спрямування. Докладно розглянуто визначальні характеристики кроссенсу, рефреймінгу, сторітелінгу і дебатів, а також запропоновано прикладні варіанти їх реалізації для майбутніх працівників правоохоронних органів. Застосування проаналізованих методів творчого навчання позитивно впливатиме на вдосконалення мовних, мовленнєвих і комунікативних навичок фахового спілкування майбутніх поліцейських, які безпосередньо формують високий рівень професійної комунікативної компетентності.

The professional activity of law enforcement officers involves active work with people, and the ability to communicate with colleagues, managers, representatives of various segments of the population ensures the success of their duties. It leads to the necessity of the language and speech skills development and improvement which are directly related to the formation of communicative competence of police officers. In modern pedagogical science various methods are described. They are aimed to develop the communicative competence of workers in a particular field. Among them, an important place is occupied by methods of creative learning. The methods of creative training in educational process have been considered in works of many scientists, however the problem of formation of policeman’s professional communicative competence by these methods have not been discovered by scientists. It is necessary to develop the outlined problem and determine the relevance of the proposed study. The author aims to consider the possibility of applying creative teaching methods in Ukrainian language classes for professional purposes which will improve the skills of professional communication of future law enforcement officers and contribute to the formation of their communicative competence. The paper uses general scientific theoretical methods including content analysis, systematization and generalization of scientific literature on the selected problem which allowed choosing the most effective methods of creative learning which should be implemented in Ukrainian language classes for future police officers. The researcher examines the defining characteristics of such methods of creative learning as cross-sense, reframing, storytelling and debate, as well as offers application options for their implementation in Ukrainian language classes for future law enforcement officers. The author concludes that application of the analyzed methods of creative training will have a positive effect on improving the language and speech skills of professional communication of future police officers, and therefore will best contribute to the formation of their communicative competence. The author of the article emphasizes the continuation of the started research in the detailed applied development of each described creative learning methods.

Рассматривает возможность использования творческих методов обучения на занятиях по украинскому языку профессиональной направленности. Детально анализируются характеристики кроссенса, рефрейминга, сторителлинга и дебатов, а также предлагаются прикладные варианты их реализации для будущих работников правоохранительных органов. Применение описанных методов творческого обучения будет оказывать позитивное влияние на усовершенствование языковых, речевых и коммуникативных навыков профессионального общения будущих полицейских, которые непосредственно формируют высокий уровень профессиональной коммуникативной компетентности.
Аpplication of creative training methods for the formation of future police officers’ professional communicative competence
Применение творческих методов обучения для формирования профессиональной коммуникативной компетентности будущих полицейских
Keywords: методи творчого навчання; creative teaching methods; методы творческого обучения; кроссенс; cross-sense; рефреймінг; reframing; рефрейминг; сторітелінг; storytelling; сторителинг; дебати; debate; дебаты; мовні навички; language skills; языковые навыки; професійна комунікативна компетентність; professional communicative competence; профессиональная коммуникативная компетентность; майбутні поліцейські; future police officers; будущие полицейские